PADDY DRYING IN MIXED ADSORPTION DRYER WITH ZEOLITE: DRYING RATE AND TIME ESTIMATION - Mochammad Djaeni; Dewi Ayuningtyas; Nurul Asiah; Hargono Hargono; Ratnawati Ratnawati; Wiratno Wiratno; Jumali Jumali (Dept. of Chemical Engineering, Diponegoro University, 2013)
Recently, the main problem of the rice stock and distribution in Indonesia is the quality degradation as indicated in unpleasant odor (smelly), stained, yellowness, and high percentage of broken rice. This is due to the low of paddy quality dried by from either direct sunlight or conventional fluidized bed dryer. As a result, the paddy cracks and breaks easily during milling in which causes the storage life being shorter as the enzymatic degradation by germ or fungi occurs. Air dehumidified with zeolite at drying medium temperature is potential to improve the quality of paddy. Zeolite is a material having high affinity to water vapor. In this case, the paddy and zeolite was mixed and fluidized with the air. The air will evaporate water from paddy, and at same time, the zeolite will adsorb water from air. Hence, the humidity of dryer can be kept low in which improves the driving force for drying. This work discusses the effect of presence of zeolite in the dryer, operational drying temperature, air velocity and relative humidity on drying rate of paddy. The results showed that increasing of zeolite as well as operational temperature increased the drying rate. In addition, using the model, the air dehumidification with zeolite and increase of air velocity can speed up drying time significantly at operational temperature below 80oC. This condition is very suitable for paddy drying since the quality degradation can be avoided.